POSITIONING INDONESIAN ISLAMIC HIGHER-EDUCATION VIS-A-VIS GLOBALISATION: ORGANISATIONAL–RESILIENCE DYNAMICS - Erika Setyanti Kusumaputri; Hanifah Latif Muslimah; Adib Ahmad; Mayreyna Nurwardani (Jurnal Cakrawala Pendidikan, 2021)
In the present era of globalisation, higher-education institutions are required to focus on innovation to deal with the various challenges. Considering what Islamic higher-education institutions in Indonesia, have achieved in recent times, they face an uphill struggle to compete at the global level. This study aimed at identifying and analysing the dynamics of resilience for globalisation in a state Islamic–University in Indonesia. The results of studies on the management of Islamic tertiary institutions, specifically on organizational resilience, are very difficult to find. This study used the qualitative analysis method of a case-study and comprised in-depth interviews with key people concerned with the management of the university, observation, and secondary data namely academic documents, photos, and information from the university’s official website. The findings showed the university’s continuous efforts to improve not only the academic community’s management skills, knowledge, and expertise but also the implementation of international-curriculum standardization and cooperation with overseas universities. These actions cannot be separated from obstacles faced by university from within and without particularly in terms of funding-related policies. The university’s program-based innovations which are yet to be carried out by other Islamic-universities in Indonesia indicate this institution’s initiative to break the obstacles.